First Evidence of Function for Schistosoma japonicumriok-1 and RIOK-1 - Mudassar N. Mughal (Pathogens, 2021)
Protein kinases are known as key molecules that regulate many biological processes in animals. The right open reading frame protein kinase (riok) genes are known to be essential regulators in model organisms such as the free-living nematode Caenorhabditis elegans. However, very little is known about their function in parasitic trematodes (flukes). In the present study, we characterized the riok-1 gene (Sj-riok-1) and the inferred protein (Sj-RIOK-1) in the parasitic blood fluke, Schistosoma japonicum. We gained a first insight into function of this gene/protein through double-stranded RNA interference (RNAi) and chemical inhibition. RNAi significantly reduced Sj-riok-1 transcription in both female and male worms compared with untreated control worms, and subtle morphological alterations were detected in the ovaries of female worms. Chemical knockdown of Sj-RIOK-1 with toyocamycin (a specific RIOK-1 inhibitor/probe) caused a substantial reduction in worm viability and a major accumulation of mature oocytes in the seminal receptacle (female worms), and of spermatozoa in the sperm vesicle (male worms). These phenotypic alterations indicate that the function of Sj-riok-1 is linked to developmental and/or reproductive processes in S. japonicum.